Tingkat Pengetahuan Ibu tentang Gizi serta Status Gizi Balita - Jauhari, M Thonthowi; Ardian, Junendri (Lembaga Pengembangan Kinerja Dosen, 2024)
The toddler age is an age that is vulnerable to experiencing nutritional problems. In toddlers, there are many nutritional problems in the form of malnutrition and even stunting. Factors causing nutritional problems in toddlers are caused by suboptimal nutritional intake. Optimal nutritional intake in toddlers is influenced by the level or low knowledge of mothers about nutrition. This study aims to analyze the relationship between the level of knowledge about nutrition of mothers of toddlers and the nutritional status of toddlers. The research method uses an analytical observational method with a cross sectional design. The respondents to this research were 61 mothers and their toddlers. Collecting data on the mother's level of knowledge used a 20-question questionnaire, measuring the nutritional status of toddlers using the TB/PB index. Data analysis was carried out using the chi-square test. The results of research statistical tests show that there is a significant relationship between the level of maternal knowledge about nutrition and the nutritional status of toddlers, obtained p value = 0.002 < 0.05.